Homocysteine and related genetic polymorphisms in Down's syndrome IQ. Issue 5 (15th April 2005) - Guéant, J-L; Anello, G; Bosco, P; Guéant-Rodríguez, R-M; Romano, A; Barone, C; Gérard, P; Romano, C
Abstract : Objective: Down's syndrome (DS) is the most frequent genetic cause of Alzheimer-type dementia. Its metabolic phenotype involves an increased trans-sulphuration of homocysteine. The aim of the present study was to investigate the influence of homocysteinaemia (t-Hcys), folate, vitamin B12, and related polymorphisms on intelligence quotient (IQ) in DS. Methods: The IQ of 131 patients with trisomy 21 from a specialist centre in Sicily was determined and classified according to DMS-IV. The effects of age, folate, vitamin B12, t-Hcys, and genetic polymorphisms on IQ were evaluated separately and in combination using regression analyses. Results: IQ was significantly lower in DS patients with t-Hcys >7.5 μmol/l (median) and in those who were carriers of methylenetetrahydrofolate reductase (MTHFR) 677 T allele and of methylenetetrahydrofolate reductase 677 T and transcobalamin 776 G combined alleles (p = 0.0013, p = 0.0165, and p = 0.0074, respectively). The IQ correlated significantly with t-Hcys and folate in single and multiple regression analyses, independently of age. In addition, t-Hcys >9.6 μmol/l (upper quartile) was found to be associated with low IQ (<40, median of study group) with an odds ratio of 2.61 (p = 0.0203). The odds ratio was increased by threefold in carriers of MTHFR 677 T allele. The MTHFR 677 T allele/ transcobalamin 776 G allele combination was associated with the risk of DS patients to have an IQ less that the median with an odds ratio of 2.68 (95% CI 1.26 to 5.70, p = 0.0104). Conclusion: This study found evidence of an association between t-Hcys and MTHFR 677 T and transcobalamin 776 G alleles with IQ in patients with DS. The association may be related to a defective remethylation of homocysteine, affecting IQ.